2012
DOI: 10.1002/gcc.22030
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 20 genes at chromosome band 12q13: RACGAP1 and MCRS1 overexpression in nonsmall‐cell lung cancer

Abstract: Chromosomal aberrations at 12q13 are frequent in nonsmall-cell lung cancer (NSCLC). Here, we examined mRNA expression of 20 genes within chromosome band 12q13 by quantitative real-time polymerase chain reaction in NSCLC. Of the 20 genes, nine were upregulated, while two genes were downregulated. Among the nine upregulated genes, mRNA values of RACGAP1, MCRS1, EIF4B, WNT1, and PTGES3 were significantly higher in NSCLCs compared with normal lung tissues. Subsequently, overexpressions of RACGAP1 and MCRS1 were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…Little is known about the biological function of Racgap1 in B-lymphoma, but its value as biomarker for early recurrence and heightened aggressiveness of solid cancers is increasingly being recognized [25,26,27]. Racgap1 , a positive regulator of Rac activity, has been reported to play an important role in cytokinesis [28], differentiation of myeloid cells [29] and, interestingly, increased production of reactive oxygen species (ROS) [30].…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the biological function of Racgap1 in B-lymphoma, but its value as biomarker for early recurrence and heightened aggressiveness of solid cancers is increasingly being recognized [25,26,27]. Racgap1 , a positive regulator of Rac activity, has been reported to play an important role in cytokinesis [28], differentiation of myeloid cells [29] and, interestingly, increased production of reactive oxygen species (ROS) [30].…”
Section: Discussionmentioning
confidence: 99%
“…This is also the first report to show that overexpression of tumor-associated RacGAP1 is directly controlled by E2F7, which itself is known to be overexpressed in SCC and to induce drug resistance (15). Overexpression of RacGAP1 has been reported in high-grade meningiomas, non-small cell lung cancer, gastric cancer, hepatocellular carcinoma, breast cancer (24,38,(42)(43)(44) as well as in the more aggressive tumor phenotypes of epithelial ovarian cancer, highgrade breast cancer, and invasive cervical cancer (45)(46)(47). However, it is unknown whether the overexpression of RacGAP1 in these tumors is linked to overexpression of E2F7.…”
Section: Discussionmentioning
confidence: 64%
“…In early studies, we screened novel cancer-related genes and found that microspherule protein 1 (MCRS1) was overexpressed in lung cancer (Liang et al, 2013). Subsequently, we confirmed the overexpression of MCRS1 was associated with the cellular proliferation, EMT, and metastasis (Liu et al, 2014).…”
Section: Oncogene–mirna–tsg Network Hypothesismentioning
confidence: 99%